Medical Students’ Online Learning Problems of Learning English on the Covid-19 Pandemic - Sri Wahyuni; Rindilla Antika (Tarbiyah: Jurnal Ilmiah Kependidikan)
This study aimed to identify medical students’ problems in following English online learning on the Covid-19 pandemic. This study used qualitative descriptive research using a survey design. The participants of this research were 183 medical students of Baiturahmah University who taking English subject. Data was collected through questionnaires that spread by using Google Forms. The data were analyzed quantitatively. The results of the study showed that the medical students had problems in English online learning during the Covid-19 pandemic. The problems faced were the networks, the limited quota, the environment, the motivation, and the comprehension of materials. It is hoped that the institutions, the lecturers, and the students find the solution in creating effective, conducive, and valuable learning.